THE WORK "ARK BUKHARI" IS AN IMPORTANT HISTORICAL SOURCE FOR THE STUDY OF THE BUKHARA ARK - Feruza Hayatovna Bobojonova; D. A. Olimova (Web of Journals Publishing, 2025)
This scientific article expresses the concepts of general information about the work of "Ark Bukhari". The history of the writing of this valuable work is described in a different way from other works. This work is comprehensive and based on historical facts, and its authors were able to describe the structure and internal life of the Ark in the late 19th and early 20th centuries in an impartial and correct political assessment.
Keywords: Ark, M.S. Andreev, O.D. Chekhovich, museum, expedition, Nasiriddin Tora,